Technology of Repairing the Active Main Pipeline Using Braze-Welded Couplings - Григорій Тимчик; Олександр Подолян; Катерина Сергієнко (KPI Science News, 2023)
Background. During operation, the main pipeline needs to be repaired. During periodic diagnostics of the pipeline state defects are detected, some of which are unacceptable. The classic repairing method, that involves the shutdown of the pipeline with subsequent replacement of its defective spots, requires significant financial costs and is associated with a forced  pipeline outage and environmental violation.